Growth and Yield of Soybean Plants (Glycine Max (L.) Merrill) in Podsolic Soil With Arbuscular Mycorrhizal Fungi and Synthetic Zeolite From Fly Ash as Soil Amendments - Mahmudin, Mahmudin; Nelvia, Nelvia; Deviona, Deviona (Devotion : Journal of Research and Community Service, 2023)
This research aims to understand the interaction between Arbuscular Mycorrhizal Fungi (AMF) and zeolite fly ash (FA) from coal and their impact on soybean productivity in Podzolic soil. The study was conducted in Aur Sakti Village, Tambang District, Kampar Regency, and the Soil Science Laboratory and Plant Ecophysiology Laboratory of the Faculty of Agriculture, University of Riau, over a four-month period from March to June 2022. The experiment employed a completely randomized design (CRD) with two factors: FA zeolite doses (Z0-Z3) and AMF doses (M0-M2). The results of the study indicate that the interaction of AMF Glomus sp or Gigaspora sp at 10 g per plant with FA zeolite at a dose of 1.5 g per plant enhances plant growth and soybean yield most optimally. FA zeolite at a dose of 1 g per plant also effectively improves soybean yield in terms of the weight of 100 seeds. Specifically, the application of FA zeolite at a dose of 1.5 g per plant yields the best results in terms of plant height, number of productive branches, flowering and harvesting age, number of seeds per plant, weight of seeds per plant, and weight of 100 seeds, compared to treatments without zeolite, with zeolite FA doses of 0.5 and 1 g per plant. The application of AMF Glomus sp and Gigaspora sp, each at 10 g per plant, also enhances the growth and yield of soybeans compared to treatments without AMF.